Adoption of sustainable cattle practices in Olancho, Honduras: A path to climate resilience - Sandoval, Danny; Burkart, Stefan (2025)
This study examines the adoption process of sustainable cattle practices in Olancho, Honduras, a climate-vulnerable region where cattle farming supports rural livelihoods. Surveying 425 producers (participants of Heifer International Farmer Field Schools), we found that the adoption of sustainable practices remains low. Key factors influencing adoption include gender, farm size, and age, with younger producers and smallholder farms showing higher adoption rates. Women are overrepresented among non-adopters but also have a notable presence at the highest adoption level. The study recommends targeted support for women, youth, and smallholders, enhanced technical assistance, financial incentives for adoption, and gender-inclusive policies to encourage greater participation in sustainable cattle practices. Additionally, improving access to technology and strengthening monitoring and evaluation systems are critical to scaling up sustainable farming practices. These interventions will help improve environmental outcomes and enhance the livelihoods of cattle producers in Olancho and similar regions.